Coupling of dual mass-transferring white dwarf binaries as a variable gravitational-wave emitter. Issue 4 (6th July 2020) - Seto, Naoki
ABSTRACT: We study evolution of a hierarchical four-body (2 + 2) system composed by a pair of mass-transferring white dwarf binaries. Applying a simplified model around the synchronous state of two inner orbital periods, we newly find that the four-body system could settle down to a limit cycle with a small period gap. The period gap generates an amplitude variation of emitted gravitational waves as a beat effect. Depending on model parameters, the beat period could be 1–10 yr and a large amplitude variation might be observed by space gravitational-wave detectors.